Arthroscopic Primary Repair of Proximal Anterior Cruciate Ligament Tears With Suture Augmentation - Harmen D. Vermeijden MD; Jelle P. van der List MD; Gregory S. DiFelice MD (SAGE Publishing, 2021)
Background: Historically, the midterm outcomes of open anterior cruciate ligament (ACL) repair were rather disappointing, and ACL reconstruction subsequently became the surgical standard for ACL injuries. Recent studies, however, have shown that there might be a role for arthroscopic primary repair in appropriately selected patients with proximal ACL tears. Indications: Due to more prominent blood supply in the proximal ligament region, ACL repair should only be performed in patients with proximal tears and good-to-excellent tissue quality. Although all patients are potential candidates, this procedure is preferably performed acutely and in adult patients. Technique Description: First, it is identified whether a proximal tear with good tissue quality is present. Then, both ACL bundles are sutured individually from distal to proximal using a Bunnell-type pattern and a self-retrieving suture passer. The posterolateral bundle is then reattached first in anatomical fashion, using a 4.75-mm vented biocomposite suture anchor. Next, the suture anchor of the anteromedial bundle is preloaded with an internal suture tape augmentation. After anchor deployment, the suture tape augmentation is channeled through a small 2.5-mm tibial tunnel in the anterior third of the tibial ACL footprint. Finally, the suture augmentation is tensioned near full extension and fixed to the tibia's anteromedial cortex using single suture anchor fixation. Results: Recently, we have published a series of the first 113 consecutive repair patients with minimum 2-year follow-up, of which 60 received additional suture augmentation. In this cohort, the overall failure rate was 13%, which was similar to 3 other studies on modern-day ACL repair (range: 5%-15%). Subgroup analysis showed that the failure rate was much higher in patients ≤21 years (38%) but low in patients >21 years (0%). Finally, it has been shown that there is an earlier return of knee motion, complications are rare, and there is less joint awareness after ACL repair as compared with ACL reconstruction. Conclusion: Selective, modern-day, arthroscopic primary ACL repair with suture augmentation seems to be a good alternative to ACL reconstruction in carefully selected patients, which include patients with proximal tears and good tissue quality and aged ≥22 years.